Effectiveness of Mouthwashes in Managing Oral Diseases and Conditions: Do They Have a Role? - Colman McGrath; Janet Clarkson; Ann-Marie Glenny; Laurence J. Walsh; Fang Hua (Elsevier, 2023)
Antimicrobial mouthwashes are considered to reduce dental plaque biofilm and thus the potential to prevent plaque-induced oral diseases, particularly periodontal diseases. The effectiveness of mouthwashes relates to this antiplaque role, as well as, their tooth-whitening potential and ability to mask/mange malodour (halitosis). There is also a growing interest in the use of mouthwashes as an adjunctive measure in post surgical and post-dental care, while the COVID-19 pandemic has given a new lease of life to mouthwashes as an oral antispetic that may be useful in reducing the oral viral load. The mode of action of mouthwashes varies, depending on their active ingredients, concentrations, and mode and frequency of use, as does their potential effectiveness. This article aims to provide a narrative overview of the evidence of the effectiveness of the most widely used mouthwashes in managing oral diseases, oral conditions, and adjunctive care roles.